Charge transport in SiCN/Si heterostructures. (1st June 2022) - Sukach, A.V.; Tetyorkin, V.V.; Тkachuk, А.І.; Kozak, A.O.; Porada, O.K.; Ivashchenko, V.I.
Abstract: The steady-state space-charge limited (SCL) current was investigated in amorphous silicon carbonitride ( a -SiCN) films deposited on single crystal silicon substrates of p -type conductivity by plasma-enhanced chemical vapor deposition (PECVD) technique. The influence of the deposition time and thermal annealing on the mechanism of the SCL current is studied. It is shown that the SCL current can be limited by shallow or deep traps, depending on the preparation condition. Experimental evidences are obtained that the traps in the films under study are associated with dangling bond defects, presumably due to the decomposition of Si–H bonds. Band and trap parameters (mobility of electrons, density and energy of trap states) are estimated from the SCL current measurements. Highlights: The SCL current limited by shallow or deep traps, are studied in as-deposited and annealed a -SiCN films on p- type c- Si. The band and trap parameters of a -SiCN films were determined. The deep traps are suggested to be related to the silicon dangling-bond states.